Cuộc đời của Landau (1908-1968) - Maya Bessarav (Thanh Niên, 1978)
Soviet physicist. Did fundamental theoretical work in low-temperature physics, predicting properties for a rare helium isotope that scientist are still trying to verify; awarded Nobel Prize in physics, 1962